Nanoemulsion-based plant essential oil formulations: in vitro evaluation of pesticidal activity against ectoparasites in poultry - Anuwat Lakyat; Jarongsak Pumnuan; Thanaporn Doungnapa; Sudjai Phutphat; Somsak Kramchote; Kamronwit Thipmanee (My University, 2023)
Ectoparasite infestations significantly impact the health and productivity of poultry. Chemical applications, although common for pest control, lead to pesticide residues and parasite resistance in poultry. Nanoemulsion-based plant essential oil formulations (NEOFs) provide a promising alternative for controlling poultry ectoparasites. This study aimed to assess the efficacy of NEOFs from clove, cinnamon, and turmeric essential oils (EOs) against ectoparasites, Menopon gallinae and Megninia ginglymura, under laboratory conditions. The toxicity and repellent properties of the NEOFs were examined, with the major chemical compounds of the EOs analyzed using chromatography mass spectrometer. Results identified eugenol as the dominant component in clove and cinnamon EOs (84.60 and 75.19%, respectively), while turmerone (68.46%) was the major compound in turmeric EO. NEOFs with clove:cinnamon:turmeric ratios of 4:0:0, 2:2:0, and 2:0:2 had particle size of 20.76 nm, 20.66 nm, and 89.56 nm, respectively, while those based on eugenol and turmerone standards had sizes <21.0 nm. In addition, NEOFs at 0.3% concentration with ratios of 4:0:0 and 2:2:0 achieved full control of both ectoparasites. These formulas demonstrated exceptional potency in exterminating ectoparasites, with LC
Keywords: Insect Pest Control Strategies